CFD analysis of supercritical water flow instability in parallel channels. (July 2015) - Li, Jingjing; Zhou, Tao; Song, Mingqiang; Huo, Qijun; Huang, Yanping; Xiao, Zejun
Abstract: 3-D simulation of supercritical water flow instability in parallel channels is presented. Results are obtained under different inlet temperatures and mass flows of supercritical water. Effect of asymmetrical heating power of the twin channels on system performance is also investigated. Results show that if the heating power is low, after a small disturbance the mass flow of the twin channels will get to stable state, or the mass flow within the twin channels will appear periodic oscillate. The oscillation amplitude will grow with the growing of asymmetrical heating power, but the oscillation period decreases with the growing of asymmetrical heating power. The growing of inlet mass flow will always enhance the system stability. The influence of inlet temperature to the flow oscillation is not linear. There is an inlet temperature threshold, when the inlet temperature is lower than the threshold value, the system stability will decrease with the growing of inlet temperature. But when the inlet temperature is higher than the threshold value, the system stability will increase with the growing of inlet temperature.